2015
DOI: 10.1007/s10461-015-1194-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV and Associated Risk Factors Among Long Distance Truck Drivers in Inchope, Mozambique, 2012

Abstract: This is the first integrated biological and behavioral surveillance survey among long-distance truck drivers (LDTD) in Mozambique. Using modified time-location sampling in 2012 at a key transportation junction (Inchope), we enrolled 327 male LDTD. HIV prevalence was 15.4 % (95 % confidence interval : 11.4–19.4 %, n = 318 tested). Among HIV-positive LDTD, 83.7 % did not know their status. One-third of LDTD had never tested for HIV and three-quarters had not received free condoms, lubricants or HIV literature in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 28 publications
1
44
0
2
Order By: Relevance
“…However, HIV care and treatment in cross‐border areas face many challenges not encountered to the same extent in other areas, including an influx of mobile and transient populations, patients lost to follow‐up across international borders, and patients presenting for treatment away from their home countries, which may use different treatment regimens . Taken together, these challenges imply that people with HIV who live, socialize and travel in cross‐border areas may not be optimally served by existing HIV care and treatment programmes predominantly administered through a country‐focused lens.…”
Section: Introductionmentioning
confidence: 99%
“…However, HIV care and treatment in cross‐border areas face many challenges not encountered to the same extent in other areas, including an influx of mobile and transient populations, patients lost to follow‐up across international borders, and patients presenting for treatment away from their home countries, which may use different treatment regimens . Taken together, these challenges imply that people with HIV who live, socialize and travel in cross‐border areas may not be optimally served by existing HIV care and treatment programmes predominantly administered through a country‐focused lens.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies among truck drivers in Africa have also found high HIV prevalence, including 23% among long-distance truck drivers in Nigeria (Azuonwu et al 2011), 15.4% among truck drivers in Mozambique (Botão et al 2016) and 26% among truck drivers in South Africa (Delany-Moretlwe et al 2014. Because truck drivers often cross international borders for their work (Mills et al 2012;North Star Alliance 2012;Mantell et al 2014), high HIV prevalence among female sex workers and their truck driver clients in one country can lead to HIV transmission to truck drivers from other regions or countries, and to their wives and partners at home.…”
Section: Introductionmentioning
confidence: 95%
“…Nesse sentido, a população de caminhoneiros tem sido apontada em diferentes regiões do mundo como uma população com maior risco de adquirir o HIV, devido a algumas características laborais peculiares, como a mobilidade por rotas de longa distância e não permanência em suas cidades de origem 3 , principalmente em regiões do continente africano [9][10][11][12] e asiático [13][14][15][16] .…”
Section: Introductionunclassified
“…Estudos brasileiros também têm se atentado para esta dinâmica peculiar, e apontam para fatores e questões relacionadas à vulnerabilidade de caminhoneiros ao HIV/aids [17][18][19][20][21][22] . Comumen-te, os caminhoneiros são descritos na literatura como indivíduos que se relacionam com parceiras eventuais durante as viagens de longa distância 9,15,17,18,22 . Estudos também têm apontado para existência de fatores, significados e concepções que apoiam a não utilização do preservativo nas relações sexuais desses sujeitos com suas parceiras 12,15,16,22 .…”
Section: Introductionunclassified